Fatty acid profiling reveals a trophic link between mangrove leaf litter biofilms and the post-larvae of giant tiger shrimp Penaeus monodon - WC Gatune (Inter-Research, 2014)
Shrimp ponds integrated with mangroves intercept leaf litter which may contribute to the bioenergetics of shrimps. Since fatty acids (FAs) determine the nutritive value of shrimp food, we analyzed and compared the FA profiles of post-larvae (PL) of Penaeus monodon fed with decomposing litter of Rhizophora mucronata, the associated biofilm, or a nutritionally optimized compound food. Three nutritionally important stages of decomposition (1, 5, and 10 wk) were tested. FA levels of PL at the start of the experiment were used as controls. As litter decomposed, saturated FAs decreased, whereas monounsaturated FAs (MUFAs) and polyunsaturated FAs (PUFAs) increased. PUFA concentrations were higher in biofilm than in the litter. PL fed with litter and biofilm food had higher MUFAs, arachidonic acid (ARA), and eicosapentaenoic acid (EPA) compared to PL fed with a compound food. However, PL fed with compound food had higher linoleic acid and docosahexaenoic acid (DHA). PL fed with 5 wk decomposed litter and its biofilm had a high concentration of bacterial odd carbon chain FAs. FAs in shrimp tissue reflected the FA profiles of the food sources in all treatments, with biofilm and compound food showing a better match. We conclude that (1) mangrove biofilm is a potential source of essential FAs to PL, especially providing ARA, EPA, and DHA; (2) biofilm on mangrove leaf litter may upgrade the nutritional value of PL for their consumers, including humans; and (3) efforts should be made to promote periphytic biofilms in integrated mangrove-shrimp culture practices.